Dental health empowerment for underprivileged children community in Tambisan, Lahad Datu, Sabah - Ghazali, Ahmad Badruddin; Abdullah Thaidi, Nur Imanina (2019)
Aim: To describe and report the activities done at PPMI (Pusat Pembangunan Minda Insan) in Tambisan, Lahad Datu, Sabah. Brief description of activities: Tambisan, located in the eastern tip of Sabah, is a controversial area among Malaysians due to Lahad Datu intrusion and a series of abduction. The village was previously given grants under KKLW to empower the local communities economically and it was done with the collaboration of a local NGO. A volunteer school to cater to local underprivileged children, which many of them did not have proper identification and cannot receive the education, medical and dental coverage from the government facilities. In 2014, the first medical and dental camp was organized by Kelab Kesihatan HALUAN, A second mini dental mission was organized with help from Pejabat Pergigian Lahad Datu in 2016, both with a military escort by ESSCOM. Conclusion: The biggest obstacles for organizing medical and dental camps in these rural areas were money, logistic, and safety. Therefore, we believe that proper and continuous education combined with strategic cooperation with many agencies to empower an underprivileged community.